The Effectiveness of Traditional Games on the Social Development of Elementary School Students in the Digital Age - Fadhilah Salsabila Riadi; Triana Lestari (Universitas Pendidikan Indonesia (UPI), 2021)
In this digital era, the way children play has changed according to the times where children play modern games more often, thereby reducing children's social interactions. Therefore, the authors are interested in discussing the effectiveness of traditional games on the social development of children in this digital era. In this study, the authors used qualitative methods based on literature studies from various relevant sources, both books, and journals. By examining these sources which then the authors interpret in this paper. The results showed that traditional games can help children's social development. because a lot of value is social skills. In addition, traditional games can be an innovation in learning and extracurricular activities. Because traditional games have a lot of value in social skills. So that the task of developing elementary school-age children starting from social adjustment and social skills that must be developed through play can be achieved. Therefore, it can be stated that this traditional game is effective for the social development of elementary school students in this digital era. Besides that, cultural values in traditional games can also be preserved.